Study of spectrum of hepatobiliary involvement in children with sickle cell disease - Dey, Ankita; Preeti Malpani; Urvashi Channa (Asian Journal of Medical Sciences, 2023)
Background: Sickle cell disease (SCD) has various complications among which one of the main organs to be affected is the hepatobiliary system ranging from mild liver function test derangements to significant hepatic abnormalities with marked hyperbilirubinemia. Aims and Objectives: We studied the spectrum of hepatobiliary involvement in children with SCD and its association with various factors. Materials and Methods: This cross-sectional observational study was conducted at M.Y Hospital Indore, a tertiary centre in central India. All old and new SCD patients under age of 18 years were enrolled sequentially, their detailed history and thorough clinical examination based on a pre-structured proforma noted. Laboratory investigations and radiological evaluation were performed to assess hepatobiliary involvement and its association with various factors was studied. Results: Two hundred and two patients with SCD were enrolled during the study period and hepatobiliary involvement was seen in 84 (41.5%) subjects. The most common acute complication was acute hepatic crisis, (20; 9.9%) followed by hepatic sequestration and intrahepatic cholestasis (2; 0.9%). Cholelithiasis was the only chronic complication, seen in 60 (29.7%) patients. Maximum number of patients (53%) were in the age group of 6.1–12 years, least (22%) belonged to 6 months–6 years of age. In our study, 52.5% of patients were females. Symptoms with hepatobiliary involvement were yellowish discoloration of eyes (39.10%), fever (36.10%), abdominal pain (20.8%), vomiting (14.4%), and bleeding (0.9%). Indirect and direct bilirubin, liver enzymes were raised, coagulation profile deranged, and the synthetic function of liver reduced. The most common USG finding was hepatomegaly, seen in 111 (54.9%) patients. Significant association between hepatobiliary involvement with higher HbS concentration, increased frequency of vaso-occlusive crisis/year, and higher transfusion requirement was noted. Conclusion: There is significant hepatobiliary involvement in patients with SCD, accounting for great morbidity and mortality requiring high degree of clinical suspicion for timely diagnosis and early treatment.